Islamic Economics Students' Perceptions of Digital Philanthropy Platforms and Their Impact on Islamic Economics Students' Interest in Donating - Habibah Nurul Fitri Fadhillah; Lucky Engraini Fitri; Ridhwan . (JOURNAL OF SHARIA ECONOMICS, 2023)
Islamic Economics Students' Perceptions of Digital Philanthropy Platforms and Their Impact on Islamic Economics Students' Interest in Donating", aims to determine students' perceptions of digital philanthropy which is now increasingly developing and to determine students' interest in donating. This research is included in qualitative research, using interviews as primary data and books, journals, current news, and previous research as secondary data. Participants in this research were 15 active students of the 2018, 2019 and 2020 Islamic Economics Study Program at Jambi University. The data processing stages in this research include editing, organizing, and drawing conclusions, and the analysis stages of this research are Unitizing, Sampling, Recording/coding, Reducing, Abductively Inferring, and finally Narrating . The results of this research are that student perceptions are quite good, but knowledge or literacy about philanthropy information and philanthropy itself is very poor. Students have an interest and interest in using and introducing digital philanthropy platforms and are positively interested in continuing to do philanthropy, and as the interview progresses, participants' interest in philanthropy becomes better. This illustrates the positive relationship between perceptions and interest.